Orientalisme dalam Adaptasi Novel Pride And Prejudice karya Jane Austen ke dalam Pride and Prejudice and Zombies karya Seth Graham Smith: Adaptation of Orientalism in Novel Pride and Prejudice by Jane Austen to Pride and Prejudice and Zombies by Seth Graham Smith - A. Nurul Amaliah Darwis; Siti Hardiyanti Amri (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This paper discusses about the adaptation of Jane Austen's Pride and Prejudice novel to the graphic novel Pride and Prejudice and Zombies using the theory of adaptation and orientalism. The aim of this study is to show the notion of Eastern values ​in the adaptation. The result of the research indicates the content change from the initial novel which exhibits the lives of British people in the 19th century to the later adding zombies character. In addition, the adaptation version also presents the parody of Eastern culture and values ​​which strongly relates to orientalism issue. The description of Eastern culture and values ​​in this novel seem to be presented the way it is, but it provides stereotypes and satires about the East having bad morals and giving negative impacts which eventuallyhumiliates Eastern nations.